Optimization of Glucomanan Extraction from Porang Flour with ATPS (Aqueous Two-Phase System) Using Factorial Design - Haryadi; Budi Santoso; Vani Mutiara Pertiwi; Tasya Alya Az-Zahra (Fluida, 2025)
Porang tubers are one of the foodstuffs rich in glucomannan content. Glucomannan is widely used in various industrial fields, one of which is pharmaceuticals. To produce pure glucomannan compounds, the method of isolating glucomannan using a two-phase water system (ATPS) solvent has been widely used. One option is isolation with a two-phase water system (ATPS) of inorganic salts ammonium sulfate and ethanol at various concentrations. This study focuses on optimizing the concentration ratio of ammonium sulfate and ethanol for the glucomannan extraction process, carried out with a factorial design and continued analysis with a response surface methodology (RSM) approach. The results of the experimental design at the composition of ammonium sulfate concentration of 17.07% w/w and ethanol of 27.07% w/w showed optimal dry extract acquisition in the two-phase water system (ATPS), with a yield of 81.07%. Characterization of the results of porang flour extract with FTIR produced stretching vibrations of the O-H group at 3427.51 cm-1 and C-O-C (glycosidic bond) at 1020.34 cm-1 and bending vibrations of the -CH functional group at 864.11 cm-1, which are specific values ​​for glucomannan compounds and using visible spectrophotometry, the glucomannan concentration was obtained at 32.67%.